Eosinophil activities modulate the immune/inflammatory character of allergic respiratory responses in mice. Issue 3 (25th November 2013) - Jacobsen, E. A.; LeSuer, W. E.; Willetts, L.; Zellner, K. R.; Mazzolini, K.; Antonios, N.; Beck, B.; Protheroe, C.; Ochkur, S. I.; Colbert, D.; Lacy, P.; Moqbel, R.; et al.
Abstract Background The importance and specific role(s) of eosinophils in modulating the immune/inflammatory phenotype of allergic pulmonary disease remain to be defined. Established animal models assessing the role(s) of eosinophils as contributors and/or causative agents of disease have relied on congenitally deficient mice where the developmental consequences of eosinophil depletion are unknown. Methods We developed a novel conditional eosinophil‐deficient strain of mice (iPHIL) through a gene knock‐in strategy inserting the human diphtheria toxin (DT) receptor (DTR) into the endogenous eosinophil peroxidase genomic locus. Results Expression of DTR rendered resistant mouse eosinophil progenitors sensitive to DT without affecting any other cell types. The presence of eosinophils was shown to be unnecessary during the sensitization phase of either ovalbumin (OVA) or house dust mite (HDM) acute asthma models. However, eosinophil ablation during airway challenge led to a predominantly neutrophilic phenotype (>15% neutrophils) accompanied by allergen‐induced histopathologies and airway hyper‐responsiveness in response to methacholine indistinguishable from eosinophilic wild‐type mice. Moreover, the iPHIL neutrophilic airway phenotype was shown to be a steroid‐resistant allergic respiratory variant that was reversible upon the restoration of peripheral eosinophils. Conclusions Eosinophil contributions to allergic immune/inflammatory responses appear to be limited to the airway challenge and not to the sensitization phase of allergen provocation models. The reversible steroid‐resistant character of the iPHIL neutrophilic airway variant suggests underappreciated mechanisms by which eosinophils shape the character of allergic respiratory responses.